Transport-Limited Growth Rates in a Mutant of Escherichia coli - Von Meyenburg, Kaspar (1971)
Mutants of Escherichia coli B/r have been selected which require increased nutrient concentrations for half-maximal growth rate. This half-saturation constant (K(m)) for growth on glucose is 10(−6) and 7 × 10(−4)m for the wild type (CP 366) and the mutant (CP 367), respectively. Similarly, the K(m) is increased for growth on many other carbohydrates (20- to 500-fold), for the anions PO(4)(3−) and SO(4)(2−) (ca. 100-fold), and for the uptake of several amino acids (20- to 50-fold). At sufficiently high concentrations of the nutrients, mutant and wild type grow equally fast. The yield in terms of cell mass per milligram of substrate is unaffected by the mutation. The phenotype of the parent is reestablished in what appears to be the reversion of a single mutation (kmt) which maps between strA and metB. The pleiotropic decrease of the affinities for transport of the various nutrients seems to be the result of a modification of the cell envelope which weakens the attachment of the various specific binding proteins to the periplasmic membrane. Since the mutant K(m) values are increased considerably, high cell densities can be reached in batch cultures at growth-rate-limiting substrate concentrations (10(7) to 10(8) cells/ml). This allows chemical analysis of the cell composition; the application of the mutant to studies of bacterial physiology as function of growth rate is discussed.